Female-limited colour polymorphism in the crab spider Synema globosum (Araneae: Thomisidae) - Ajuria Ibarra, Helena; Reader, Tom (Linnean Society, 2014)
Conspicuous colour variation, caused by the influence of the environment on phenotype, or by genetic differences among individuals, is frequently observed in nature. If genetic in origin, colour variation can facilitate the study of the mechanisms that contribute to the maintenance of true polymorphisms. Here, we describe for the first time the female-limited colour polymorphism in the crab spider Synema globosum. We look for associations between life history traits and female colour morph, and identify potential agents of selection that could influence the maintenance of the polymorphism. Our results show that the polymorphism is discrete and heritable, and that differences in colour among morphs are likely to be detectable by honeybees, birds, and conspecifics. We found limited evidence of differences among morphs in morphology and ecology, and found no differences in components of reproduction. Based on the lines of evidence obtained in this study, we suggest that selection exerted by prey, predators and/or mates is likely to influence the maintenance of the polymorphism observed in S. globosum.